Characterization of hemoglobin variants by capillary electrophoresis, UV-Vis, and FTIR Spectroscopy - Werle-Urban, Julia; Dunovska, Katerina; Podhajsky, Jakub; Cerny, Michal; Cepova, Jana; Parikesit, Arli Aditya; Bjørklud, Geir; Kotaska, Karel; Klapkova, Eva; Prusa, Richard; Werle, Egon; Kizek, Rene (Electrophoresis, 2025)
Hemoglobinopathies, hereditary disorders affecting the structure or production of hemoglobin, were detected by routine HbA1c measurements by capillary electrophoresis (CE) at the University Hospital Motol, Prague. The potential of ultraviolet-visible (UV-Vis) and Fourier-transform infrared (FTIR) spectroscopy for the detection and characterization of hemoglobinopathies was investigated. FTIR spectra were recorded with a very high resolution (0.5 cm−1) with 128 scans. The broad amide I peak, located at 1700-1600 cm−1, can be formed by superimposition of the conformational structures of hemoglobin. These secondary protein structures were subjected to mathematical analysis. The application of band narrowing techniques, followed by curve fitting and integration processes, provided the basis for the quantitative estimation of protein secondary structure. As a result, unambiguous differences in UV-Vis spectra among patients with presumably normal hemoglobin, an HbC or a hemoglobin S/hemoglobin G (HbS/HbG)-Philadelphia variant could not be demonstrated. However, FTIR spectra indicated slight differences in α-helix, β-turns, β-sheet, or random coil secondary hemoglobin structures for these mutations. In the spectral wavenumber range of 950-850 cm−1, there were some obvious FTIR differences at specific wavenumbers between patients with normal hemoglobin and those with the HbC variant. Further investigations are needed with a sufficient number of hemoglobin variants to elucidate the potency of FTIR spectroscopy for the characterization of hemoglobinopathies.
Gesehen am 30.10.2025